2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34985
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, Self-efficacy, and Student Engagement in Intermediate Mechanical Engineering Courses

Abstract: where she received her PhD in Mechanical Engineering in 2008. Since then she has taught required and elective courses covering a wide range of topics in the undergraduate Mechanical Engineering curriculum. In her work with MTEI she co-leads teaching workshops for new faculty and assists with other teaching excellence initiatives. Her main teaching interests include solid mechanics and engineering mathematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Student engagement was found to be a problem for kindergarten students in online learning (Ford et al, 2021;Maimun & Bahtiar, 2022;Saxena, 2021). Hence, Hypothesis 5 proposes that kindergarten students have low engagement during online learning.…”
Section: Student Engagementmentioning
confidence: 98%
See 1 more Smart Citation
“…Student engagement was found to be a problem for kindergarten students in online learning (Ford et al, 2021;Maimun & Bahtiar, 2022;Saxena, 2021). Hence, Hypothesis 5 proposes that kindergarten students have low engagement during online learning.…”
Section: Student Engagementmentioning
confidence: 98%
“…Early childhood education teachers observed that children's low participation levels and limited social interaction are some of the challenges found in online teaching (Ford et al, 2021). Social interactions, students' motivation in learning, and distraction in online learning during COVID-19 are some challenges observed by kindergarten and primary school teachers in another study (Kundu & Bej, 2021).…”
Section: Introduction Online Teaching and Learning During Covid-19mentioning
confidence: 93%
“…In line with students 'learning motivation as a result of introduction of the mechatronic courses, Ford, Ritz and Fisher (2020) and Makarova, et al, (2020) realized that students are motivated to learn the challenging technologies and experiences. This is due to the fact that when acquiring challenging skills, learners feel they are more advanced and can fit the industrial world.…”
Section: Introductionmentioning
confidence: 95%
“…It was further found that mechatronics engineering has attracted the attention of students simply because its mode of learning has smashed away the traditional way of learning into hands on experience. Cementing on the same idea, Ford, Ritz and Fisher (2020) agreed that the hands-on experience acquired from learning mechatronics promotes the acquisition of skills and competencies among graduates.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…In theory, students and educators came into the 2020–2021 school year with more preparation time and experience with pandemic learning and other challenging pandemic‐related conditions. However, reports indicate that many classrooms still struggled with effective pedagogy (Chen et al, 2020; Chierichetti & Backer, 2021) and student motivation (Daniels et al, 2021; Ford et al, 2021).…”
Section: Introductionmentioning
confidence: 99%